Adding red propolis to the diet of Lacaune lambs: Effects on animal health, ruminal environment, performance, and meat quality - Deolindo G.L.* (2024)
© 2024 Elsevier B.V.This study determined the influence of red propolis ethanolic extract in lambs' diets on the ruminal environment, animal health, and growth. Two experiments were carried out to achieve these objectives. Pilot study: Twenty-four female Lacaune lambs were divided into four groups, with three replicates and two animals per replicate (pen): T0 (Control), TP1.3, TP2.7, and TP5.3, representing 0, 1.3, 2.7, and 5.3 mL of propolis extract per animal/day, respectively. The highest daily weight gain was observed in lambs that consumed 2.7 mL of propolis extract per day, and they also had the lowest feed conversion rate compared to the control. Lower total leukocyte counts were observed in lambs that consumed propolis extract compared to control due to lower granulocyte and lymphocyte counts. Ceruloplasmin and C-reactive protein levels were lower in the serum of lambs that consumed propolis compared to the control. Lambs that consumed 1.3 and 2.7 mL of propolis extract had lower TBARS levels than the control. The effect of treatment was observed for ruminal pH, which was higher in lambs that consumed propolis extract than in control. A lower concentration of short-chain fatty acids was observed in lambs that consumed propolis than the control due to lower concentrations of acetic and butyric acid. In experiment II, 36 male Lacaune lambs were selected and divided into two groups: MONENSIN (23.45 ppm of monensin per kg/dry matter (DM)) and PROPOLIS (3.8 mL of propolis per animal/day). The animals that consumed propolis extract had greater body weight, weight gain, and average daily gain. These also had a shorter time to reduce methylene blue, thus demonstrating more significant bacterial activity in the rumen. Furthermore, they had lower counts of Escherichia coli, total coliforms, and Enterobacteria. The meat's fatty acid profile in animals fed the red propolis extract showed higher concentrations of monounsaturated fatty acids. In conclusion, adding red propolis extract to the concentrate increased weight gain, average daily gain, and oxidative balance with an antimicrobial and anti-inflammatory effect.